Epidemiology of lung cancer in a central India population: a single tertiary cancer centre 5-year prospective study - Rawat, Shyam Ji; Kotwal, Ekta; Patel, Lalit Mohan; Uikey, Garima; Ramachandran, Sindhuja; Hindoliya, Gaurav (International Journal of Research in Medical Sciences, 2025)
Background: Globally, there have been varied changes in trends of lung cancer epidemiology depending on the geographic region, gender, histological subtype, and incidence. Also, there is a dearth in our current understanding of the changing epidemiological trends of lung cancer among Indian patients. Indian epidemiological data on lung cancer are limited, particularly in the central region. Methods: We conducted a 5-year prospective study (January 2020-December 2024) at the Department of State Cancer Institute, Jabalpur (Madhya Pradesh), to evaluate the demographic and clinico-radiological profiles of primary lung cancer in Central India. Cases with confirmed histological or cytological diagnoses were reviewed, collecting data on demographics, risk factors, residence, histological subtype, and stage at presentation. Results: A total of 546 patients (median age: 58.4 years; male-to-female ratio: 3.9:1) were included, with 60% smokers and 68.5% from rural areas. Most of the patients presented with non-small-cell carcinoma (NSCLC), with squamous cell carcinoma being the most common histological subtype (49.6%), followed by adenocarcinoma (34.6%), undifferentiated carcinoma (2.5%), and large-cell carcinoma (1.8%). Small-cell lung carcinoma accounted for 9.5% of cases. Over half of the patients (57.4%) presented with stage IV disease at diagnosis. Common metastatic sites included the pleura, liver, brain, bone, and adrenal glands, with bone metastases more commonly observed in smokers. Conclusions: A significantly high proportion of lung cancer patients in Central India are smokers. Passive smoking is also a risk factor in our region. Squamous cell carcinoma remains the predominant subtype.